STRATEGI ADVOKAT DALAM MENGATASI SENGKETA TANAH WARISStrategi Advokat Lembaga Bantuan Hukum Mustika Bangsa dalam Mengatasi Sengketa Tanah Waris di Lampung - Zidan, Muhammad; Murdiana, Elfa; Ningsih, Rahmah; Setiawan, Wahyu (Al-Mizan (e-Journal), 2024)
This research provides a comprehensive picture of the experience of Mustika Bangsa Legal Aid Institute advocates in resolving inheritance land disputes. This paper focuses on the formulation of advocates' strategies, discussing the various rarities and approaches used by advocates to effectively resolve inheritance disputes. In contrast to previous studies, which mostly discuss the role of advocates, this study centers on the concept of strategies used by advocates in resolving inherited land disputes.  A strong and structured strategy is key to achieving the desired outcome in the legal process. This study uses qualitative research for the inquiry process in investigating scientific and humanitarian issues with different traditions. The qualitative design enabled the author to map texts that speak of advocates' strategies, disputes, and legacy landscapes experienced in the context of this study. The results of the study emphasize the importance of advocates' strategies in achieving desired outcomes in the legal process. The research shows that a well-planned strategy can significantly increase the effectiveness of resolving disputes, evidenced by the satisfaction of clients assisted by Mustika Bangsa Legal Aid Institute in Metro. Through this research, the author hopes to contribute to broader efforts to create effective and sustainable advocate strategies in inheritance dispute resolution